1999
DOI: 10.1086/314608
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing ofNeisseria gonorrhoeaeCausing Repeated Infections: Evolution of Porin during Passage within a Community

Abstract: Thirty-three Neisseria gonorrhoeae isolates from 15 persons infected multiple times with the same serovar were compared using por gene sequencing, opa-typing, and arbitrarily primed-polymerase chain reaction. All three molecular techniques were more discriminatory than serotyping and identified differences between some isolates belonging to the same serovar. Although there were differences among Por sequences within some serovars, 10 of 15 subjects became reinfected with gonococci expressing identical Por prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 54 publications
4
74
2
1
Order By: Relevance
“…However, the protein has shown antigenic variation over time, as revealed by the diversity of serovars (21) and porB genes (11) identified in the N. gonorrhoeae isolates derived from patients in sexual networks. Sequence analysis of porB genes has previously indicated the presence of horizontal genetic exchange, including the exchange of the entire gene or segments of the gene, as well as point mutations in the evolution of the porin during circulation within the community (3,11,14,23). However, more knowledge concerning the mechanisms and time scale by which changes in the porB genes occur is required.…”
Section: Vol 40 2002 Sequence Analysis Of N Gonorrhoeae Porb Gene mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the protein has shown antigenic variation over time, as revealed by the diversity of serovars (21) and porB genes (11) identified in the N. gonorrhoeae isolates derived from patients in sexual networks. Sequence analysis of porB genes has previously indicated the presence of horizontal genetic exchange, including the exchange of the entire gene or segments of the gene, as well as point mutations in the evolution of the porin during circulation within the community (3,11,14,23). However, more knowledge concerning the mechanisms and time scale by which changes in the porB genes occur is required.…”
Section: Vol 40 2002 Sequence Analysis Of N Gonorrhoeae Porb Gene mentioning
confidence: 99%
“…Conventional characterization of N. gonorrhoeae strains for epidemiological and clinical purposes is mostly based on auxotyping, serovar designation, and antibiograms. However, these phenotypic systems have some inherent limitations concerning, for instance, their discriminatory abilities and reproducibilities (12,14,15,18,27). Different DNAbased methods have thus been developed (14,19,26,28,29,30,33).…”
mentioning
confidence: 99%
“…Thus, for epidemiological and clinical purposes a highly discriminating, objective, and reproducible characterization of N. gonorrhoeae strains is essential. The widely used phenotypic characterizations of the bacterium have several limitations (10,12,13,17,24,27,28), and different molecular genetic methods have thus been developed (12,15,18,23,25,26,27,28,30,32).…”
mentioning
confidence: 99%
“…Previous genetic studies have concluded that porB gene sequencing can be used to trace the transmission of individual N. gonorrhoeae strains within the community, discriminate suspected clusters of gonorrhea cases, and confirm epidemiological connections of patients (5,12,28,31). The segments of the porB gene encoding the eight surface-exposed amino acid loops of PorB (29) exhibit the highest level of polymorphism (1,4,5,7,12,27,28,29,31).…”
mentioning
confidence: 99%
“…The introduction of PCR and high-throughput nucleotide sequencing has led to the development of several DNA-based typing methods. Two methods that are highly discriminating are the opa gene (OPA) typing method and sequencing of the porB gene (POR sequencing), which we as well as others have employed (11,16,18,22). A disadvantage of the above two methods is that variation at these loci is evolving rapidly and for reasons that are not fully understood, although immune selection plays an important role.…”
mentioning
confidence: 99%